Answers

2016-01-17T13:46:58+08:00
-m = -9
(-m = -9) x 1
m = 9


0
Please multiply by (-1) to get positive m and 9; m = 9
2016-01-17T14:00:54+08:00

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
-m + 9 = 0

*transpose 9 to the other side, making it negative*

-m = -9

*divide both sides by -1*

-m      -9
---- = ----
 -1      -1

m = 9

1 5 1